2008
DOI: 10.1186/1743-422x-5-52
|View full text |Cite
|
Sign up to set email alerts
|

Effect of influenza and pneumococcal vaccines in elderly persons in years of low influenza activity

Abstract: Background: The present prospective study was conducted from [2003][2004][2005], among all individuals 65 years and older in Uppsala County, a region with 300 000 inhabitants situated close to the Stockholm urban area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 30 publications
(42 reference statements)
1
24
1
Order By: Relevance
“…In 2 studies 15,17 there was no comparison data for influenza+pneumococcal and influenza alone, 1 study was a systematic review, 16 2 studies did not report any outcomes of interest, 18,19 and 1 study was not designed for to evaluate the elderly population 20 . The systematic review by Gilchrist et al., 16 which did not include a meta-analysis, included a total of 9 studies: 2 were RCTs and the remainder were observational studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2 studies 15,17 there was no comparison data for influenza+pneumococcal and influenza alone, 1 study was a systematic review, 16 2 studies did not report any outcomes of interest, 18,19 and 1 study was not designed for to evaluate the elderly population 20 . The systematic review by Gilchrist et al., 16 which did not include a meta-analysis, included a total of 9 studies: 2 were RCTs and the remainder were observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…Study has suggested that the concomitant administration of PPV23 and influenza vaccine may have a greater protective effect against pneumonia and influenza in the elderly than the administration of either vaccination alone 15-19 . Vaccination with both vaccines has been shown to reduce the risk of hospitalization more than if only one or the other was administered 18,20 . Pneumococcal vaccination has also been shown to reduce specific- and all-cause mortality in individuals more than 60 years of age who have received influenza vaccination 21 .…”
Section: Introductionmentioning
confidence: 99%
“…A large cohort study in the USA in elderly persons with chronic lung disease (controlling for covariates and confounders) showed that influenza vaccination alone reduced hospitalization for pneumonia by 52% and pneumococcal vaccination by 27%, but when both vaccines were administered to subjects the reduction was 63% [84]. Studies by Christenson's group have found that simultaneous administration of PPV23 and influenza vaccine can better prevent excess hospitalizations in the elderly compared to either vaccine [85][86][87]. The study reported in 2004 involved 124,702 subjects, 72,107 of which received both vaccines, 29,346 only influenza vaccine and 23,249 only the pneumococcal vaccine [85].…”
Section: Impact Of Influenza Vaccines On Secondary Bacterial Infectiomentioning
confidence: 97%
“… The 23‐valent polysaccharide pneumococcal vaccine prevents invasive pneumococcal disease in older persons and in other high‐risk groups and should be given to all adult persons at risk for pneumococcal disease [A1]. Risk factors for pneumococcal disease are age >65 years, institutionalization, dementia, seizure disorders, congestive heart failure, cerebrovascular disease, chronic obstructive pulmonary disease, history of a previous pneumonia, chronic liver disease, diabetes mellitus, functional or anatomical asplenia, and chronic cerebrospinal fluid leakage [B3]. Although smoking seems to be a significant risk factor in otherwise healthy younger adults, measures aimed at reducing smoking and exposure to environmental tobacco smoke should be preferred in this group. Revaccination, once and not earlier than 5 years after primary vaccination, should be performed in asplenic patients and can be considered in the elderly and other high‐risk groups [B3]. There are not enough data to give any recommendations concerning the use of conjugate pneumococcal vaccine in adults [442–473]. …”
Section: Preventionmentioning
confidence: 99%